2011
DOI: 10.3390/cancers3022630
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy by Kinases

Abstract: Autophagy is a process of self-degradation that maintains cellular viability during periods of metabolic stress. Although autophagy is considered a survival mechanism when faced with cellular stress, extensive autophagy can also lead to cell death. Aberrations in autophagy are associated with several diseases, including cancer. Therapeutic exploitation of this process requires a clear understanding of its regulation. Although the core molecular components involved in the execution of autophagy are well studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
140
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 196 publications
(222 reference statements)
0
140
1
Order By: Relevance
“…Mammucari et al reported that autophagy in mouse muscle was regulated by mTOR complex 2 (mTORC2, rapamycin-insensitive) rather than mTORC1 (rapamycin-sensitive), and injection of rapamycin did not induce autophagy in skeletal muscle in mice [31]. It is well established that mTORC1 directly suppresses autophagy, and mTORC2 may also regulate autophagy via Akt [32]. We did not observe a change in protein levels of p-Akt in human patient muscle cells after rapamycin treatment (data not shown) suggesting that the induction of autophagy in these cells was unlikely regulated by mTORC2-Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Mammucari et al reported that autophagy in mouse muscle was regulated by mTOR complex 2 (mTORC2, rapamycin-insensitive) rather than mTORC1 (rapamycin-sensitive), and injection of rapamycin did not induce autophagy in skeletal muscle in mice [31]. It is well established that mTORC1 directly suppresses autophagy, and mTORC2 may also regulate autophagy via Akt [32]. We did not observe a change in protein levels of p-Akt in human patient muscle cells after rapamycin treatment (data not shown) suggesting that the induction of autophagy in these cells was unlikely regulated by mTORC2-Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Based on examination of several endpoints related to the autophagy flux (31), we demonstrated that accumulation of AVs was due to inhibition of autophagic degradation rather than induction of autophagic flux. In addition, several protein kinases and core molecular proteins, required for induction of autophagy such as Akt, AMPK, mitogen-activated protein kinase (ERK, p38 and JNK) (34), Beclin 1 and Bcl-2 (35), were not obviously changed after imidazole treatment (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Although an increasing number of studies suggest that ERK is involved in modulating autophagy, the roles of ERK in autophagy are diverse (67). ERK signaling regulates the expression of autophagy and lysosomal genes by regulating the nuclear localization of transcription factor EB (TFEB) (63).…”
Section: Discussionmentioning
confidence: 99%